The Block-Element Method in Expansion of the Solutions of Complex Boundary-Value Problems in Mechanics - Babeshko, V. A.; Evdokimova, O. V.; Babeshko, O. M.; Evdokimov, V. S. (Doklady. a journal of the Russian Academy of Sciences. Physics, 2020)
An exact solution in the first quadrant of a plane boundary-value problem of the second kind for the dynamic Lamé elasticity equations is constructed, probably for the first time, and is expanded in terms of solutions of boundary-value problems for the Helmholtz equation. These solutions are presented in the form of packed block elements.